High-wear-resistance inorganic non-stick coating as well as preparation method and application thereof

By using silicon sol and silicone to form an inorganic ceramic coating, and adding wear-resistant fillers and non-stick additives, the problem of the reduction of non-stickness of existing non-stick coatings under high temperature and friction conditions is solved, and the development of a new inorganic non-stick coating with high wear and high temperature resistance is achieved.

CN119875399AActive Publication Date: 2025-04-25HANGZHOU JIHUA POLYMER MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411931330.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The non-stick coatings have rapidly decreased non-stick properties under high temperature and friction conditions, and have a potential threat to the environment and human health. It is necessary to develop new inorganic non-stick coatings that are highly wear-resistant and high temperature resistant.

Method used

Silicone sol and silicone are used as the main raw materials to form an inorganic ceramic coating through solvent-gel reaction, and wear-resistant fillers and non-stick additives are used to form a high hardness and high wear-resistant coating. This coating does not require organic solvents, and the preparation process is simple and environmentally friendly.

Benefits of technology

The coating has good non-stickness and wear resistance at high temperatures, can maintain stable heat resistance below 400°C, and is smoke-free and toxic gases during combustion, has high adhesion and hardness, and is easy to clean the surface.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of coatings, and discloses a high-wear-resistance inorganic non-stick coating as well as a preparation method and application thereof. The high-wear-resistance inorganic non-stick coating comprises a primer coating and a coating, wherein the primer coating comprises 50-75 parts of silica sol color paste, 10-20 parts of siloxane, 1-3 parts of an acid catalyst, 3-7 parts of a silane coupling agent, 1-2 parts of a flatting agent and 2-5 parts of a non-stick aid; the finish paint comprises the following components in parts by weight: 45-70 parts of silica sol, 13-21 parts of siloxane, 1-3 parts of an acid catalyst, 1-2 parts of a flatting agent and 2-5 parts of a non-stick aid; in the primer coating, the silica sol color paste is prepared from the following raw materials in parts by weight: 40 to 70 parts of silica sol, 10 to 15 parts of toner, 10 to 20 parts of anti-cracking ceramic filler and 1 to 5 parts of wear-resistant filler. The high-wear-resistance inorganic non-stick coating comprises independent primer coating and finish coating, the coating is free of organic solvent addition, practical, environmentally friendly and easy to produce and has the advantages of being high in hardness, good in non-stick performance after high wear resistance and resistant to high temperature, the preparation method is simple, and large-scale production is easier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a highly wear-resistant inorganic non-stick coating and a preparation method and application thereof. Background Art

[0002] Non-stick coating is an important chemical product. It is a coating material with low surface energy and anti-adhesion properties. It can be applied to iron, steel, and aluminum surfaces. It has good non-stick properties and can be used to fry eggs directly at 170-210°C without adding cooking oil and it is easy to fall off. Non-stick coating not only has good non-stick properties, but also has properties such as resistance to cold and heat shock and wear resistance. The coating can be used to modify the surface of the metal surface to improve the performance of the base material and extend the service life of the metal base material.

[0003] Non-stick coatings can be divided into two categories: organic non-stick coatings and inorganic non-stick coatings, which are widely used in the field of cookware. At present, most of the coatings of non-stick cookware on the market are fluoropolymer resin coatings such as polytetrafluoroethylene. Although it has a much smaller surface tension than other solid materials, it has a certain impact on the environment and even human health. For example, PFOA is a necessary additive in the production process of Teflon coatings. It may decompose at high temperatures and release many harmful gases, causing the death of some animals with sensitive respiratory tracts. Moreover, its chemical properties are relatively stable. It will exist for a long time in the human body and the natural environment. Its toxicity to the human body has not yet been determined. Now the US Environmental Protection Agency has decided to order eight chemical companies including DuPont to gradually reduce or even stop using the core ingredient perfluorooctanoic acid PFOA required to manufacture Teflon coatings. Therefore, inorganic coatings will gradually replace organic coatings.

[0004] On the other hand, the bonding force between polyfluororesin and the base material of cookware is relatively weak. When cooking and washing pots in daily life, the coating is easy to fall off when it comes into direct contact with the spatula and scouring pad. Although the coating has excellent non-stick properties, the non-stickiness will decrease rapidly after multiple frictions, and the non-stick pan will lose its non-stickiness. Therefore, it is necessary to make necessary improvements in terms of raw material formulation and preparation process to meet the requirements of actual applications. In addition, the high temperature resistance of polyfluororesin coating is also very weak, and it usually reaches its use limit at around 260°C. Therefore, it is necessary to develop a new type of non-stick coating with high wear resistance, good non-stickiness and high temperature resistance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a highly wear-resistant inorganic non-stick coating and a preparation method and application thereof. The highly wear-resistant inorganic non-stick coating of the present invention comprises an independent primer coating and a topcoat coating, the coating has no organic solvent added, is practical and environmentally friendly, and is simple to produce. It has the advantages of high hardness, good non-stick properties after high wear resistance, and high temperature resistance, and the preparation method is simple, which is easier to mass-produce.

[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a highly wear-resistant inorganic non-stick coating, which comprises the following raw materials in parts by weight: Primer coating: 50-75 parts of silica sol color paste, 10-20 parts of siloxane, 1-3 parts of acid catalyst, 3-7 parts of silane coupling agent, 1-2 parts of leveling agent, 2-5 parts of non-stick additive.

[0007] Topcoat: 45-70 parts of silica sol, 13-21 parts of siloxane, 1-3 parts of acid catalyst, 1-2 parts of leveling agent, 2-5 parts of non-stick additive.

[0008] The silica sol color paste comprises the following raw materials in parts by weight: 40-70 parts of silica sol, 10-15 parts of color powder, 10-20 parts of anti-crack filler and 1-5 parts of wear-resistant filler.

[0009] The highly wear-resistant inorganic non-stick coating of the present invention is divided into independent primer coating and topcoat coating. Among them, the primer coating is the component that mainly improves the appearance effect of the coating. It can provide the color (silica sol color paste) required by the user, and fill the pores on the surface of the substrate, so that the coating is smoother and flatter, and the glossiness of the coating is improved. At the same time, after the primer coating fills the pores of the substrate, it has many anchor points with the substrate, which can further increase the contact surface with the substrate, thereby improving the adhesion of the coating. The topcoat coating of the present invention, as the part in direct contact with the external environment, has excellent wear resistance, can ensure the service life of the cooker, and at the same time it has good chemical inertness, can effectively withstand the erosion of chemical substances such as acids, alkalis, and salts, and has lower surface energy, which can effectively reduce the adhesion of pollutants.

[0010] Specifically, in primer coatings and topcoat coatings, the present invention uses silica sol and siloxane as the main raw materials, and can form an inorganic ceramic coating through a solvent-gel reaction under the action of an acid catalyst, and then utilizes the wear-resistant filler in the coating to enable the coating to withstand tens of thousands of wear-resistant tests. Among them, siloxane undergoes a hydrolysis reaction with water during the aging process, converting the alkoxy group into a hydroxyl group, which is then more likely to undergo a dehydration condensation reaction with the hydroxyl group of the silica sol or the hydroxyl group of the remaining hydrolyzed siloxane, and continuously reacts to form a network structure with Si-O-Si as the skeleton. During this period, the anti-crack filler and wear-resistant filler in the silica sol color paste are also uniformly embedded in the network, and the water in the coating is removed under high-temperature baking, so that the condensed hydroxyl groups further condense, thereby forming a dense, high-hardness, and high-wear-resistant coating, making the coating unbreakable. Therefore, the high wear-resistant inorganic non-stick coating of the present invention has better wear resistance and high temperature resistance than the polyfluororesin coating. It not only has excellent non-stick properties after being rubbed 20,000 or more times with a scouring pad under a force of 15N, but also does not leak the substrate after being rubbed 120,000 or more times. It has relatively stable heat resistance below 400°C, is smokeless, has no toxic gas, and does not change color when burning. The coating does not change significantly when the temperature changes suddenly. The adhesion can reach level 0, the hardness can reach 9H, and the surface is easy to clean.

[0011] Further preferably, in the silica sol color paste: the silica sol is selected from alkaline silica sol and acidic silica sol; the color powder is inorganic color powder such as titanium dioxide, carbon black, and iron oxide; the anti-crushing filler is selected from whisker silicon, whisker aluminum oxide, and whisker silicon nitride; the wear-resistant filler is selected from silicon carbide and corundum.

[0012] Preferably, in the primer coating: the siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; the acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; the leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; the non-stick additive is selected from methyl silicone oil and low molecular weight hydroxyl-terminated methyl silicone oil (molecular weight between 300 and 2000); the silane coupling agent is selected from KH-550, KH-560 and KH-570.

[0013] Preferably, in the topcoat coating: the silica sol is alkaline silica sol; the siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; the acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; the leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; the non-stick additive is selected from methyl silicone oil and small molecular weight hydroxyl-terminated methyl silicone oil (molecular weight between 300 and 2000).

[0014] In a second aspect, the present invention provides a method for preparing a highly wear-resistant inorganic non-stick coating, which specifically includes the following steps: 1) Preparation of a primer coating: mixing a silica sol color paste with an acid catalyst, making the pH in the silica sol system suitable for maturation, adding a leveling agent, a silane coupling agent, a non-stick aid and siloxane, stirring and maturation, after the siloxane is added to the system, it first undergoes a hydrolysis reaction under the catalysis of an acid to generate silanol groups, and the silanol groups react with the hydroxyl groups of the silica sol itself, the hydroxyl groups obtained by hydrolysis of the remaining siloxanes or the hydroxyl groups of the non-stick aid to undergo a dehydration condensation reaction to generate a high-strength Si-O-Si bond, and as the maturation continues, this spatial network structure is formed, and the filler in the color paste is interspersed therein to obtain a primer coating.

[0015] 2) Preparation of topcoat: Mix the silica sol and the acid catalyst, add siloxane, leveling agent, and non-stick additive, stir and mature. The reaction process is similar to that of the primer to obtain the topcoat.

[0016] Preferably, in 1), the preparation method of the silica sol color paste comprises: mixing and ball-milling the silica sol, color powder, anti-crushing filler and wear-resistant filler to obtain the silica sol color paste.

[0017] Preferably, in 1), the stirring and aging process has a rotation speed of 240-260 rpm and a time of 4-6 hours.

[0018] Preferably, in 2), the stirring and aging process has a rotation speed of 240-260 rpm and a time of 4-6 hours.

[0019] In the third aspect, the present invention provides the use of the above-mentioned highly wear-resistant inorganic non-stick coating in the preparation of a non-stick coating for cookware, comprising the following steps: sandblasting the cookware substrate, in order to provide more anchor points between the primer and the substrate and increase its adhesion, and then cleaning it, in order to remove dust and grease on the surface of the substrate and ensure that there are no particles and shrinkage holes after the coating is dried, preheating can effectively remove moisture and condensate on the surface of the substrate, which is conducive to thermal activation of the surface and promotes the physical and chemical reaction between the substrate and the coating. When spraying the coating, first spray at least 2 layers of primer coating, wet spray at least 1 layer of topcoat coating directly on the primer without surface drying, and sinter after surface drying. If surface drying is not performed, the moisture in the coating cannot be fully volatilized, which may cause the coating to crack and collapse easily. During the high-temperature sintering process, the unreacted silanol groups will further condense, and the silanol groups connected to the substrate will also condense with the hydroxyl groups on the substrate, and are connected in the form of bonding, which is very firm. After sintering, place it indoors and slowly cool it down to obtain a highly wear-resistant inorganic non-stick coating.

[0020] In the method of the present invention, the preparation process of the primer coating and the topcoat coating is simple. The raw materials only need to be put into a reaction bottle once for maturation and filtration before use. The operation is simple and no heating, temperature control and other operations are required, which saves energy. After spraying the primer coating, there is no need for surface drying. The topcoat coating can be directly sprayed and then put into drying, which is fast and convenient.

[0021] Preferably, the preheating temperature is 40-60°C.

[0022] Preheating can effectively remove moisture and condensation on the surface of the substrate, which is beneficial to thermal activation of the surface and promotes the physical and chemical reaction between the substrate and the coating. However, the preheating temperature cannot be too high or too low. Too high a temperature will cause the coating to become rough and the glossiness to decrease, while too low a temperature will cause the coating to sag and produce shrinkage holes.

[0023] Preferably, the primer coating and the topcoat coating are pre-filtered through a 300-500 mesh filter.

[0024] Preferably, the number of spray layers of the primer coating is 2-3 layers, and the number of wet spray layers of the topcoat coating is 1-2 layers.

[0025] Preferably, the drying temperature is 140-160° C. and the drying time is 3-10 min.

[0026] Preferably, the sintering temperature is 240-280° C. and the sintering time is 5-20 min.

[0027] Compared with the prior art, the beneficial effects of the present invention are: (1) The coating of the present invention does not require the addition of organic solvents, is practical, environmentally friendly, and simple to produce. It not only has excellent non-stick properties after being rubbed 20,000 or more times with a scouring pad at a force of 15 N, but also does not leak the substrate after being rubbed 120,000 or more times. It has relatively stable heat resistance below 400°C, is smokeless when burned, does not produce toxic gases, does not change color, and has no obvious changes in the coating when the temperature changes suddenly. The adhesion can reach level 0, the hardness can reach 9H, and the surface is easy to clean.

[0028] (2) In the method of the present invention, the preparation process of the primer coating and the topcoat coating is simple. The raw materials only need to be put into the reaction bottle once for maturation and filtration before use. The operation is simple and no heating, temperature control and other operations are required, which saves energy. After spraying the primer coating, there is no need to dry the surface. The topcoat coating can be directly sprayed and then put into the drying process, which is fast and convenient.

[0029] (3) The non-stick additive of the coating of the present invention, the low molecular weight hydroxyl-terminated methyl silicone oil, is introduced into the network by dehydration condensation. Compared with physical embedding, this method can firmly fix the low surface energy groups on the coating, greatly improving the long-term non-stick performance of the coating. DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with the embodiments.

[0031] Overall embodiment First, a highly wear-resistant inorganic non-stick coating, which includes a primer coating and a topcoat coating. Specifically: The primer coating comprises the following raw materials in parts by weight: 50-75 parts of silica sol color paste, 10-20 parts of siloxane, 1-3 parts of acid catalyst, 3-7 parts of silane coupling agent, 1-2 parts of leveling agent and 2-5 parts of non-stick additive.

[0032] In some preferred implementation cases, in the primer coating: the silica sol color paste includes the following raw materials in parts by weight: 40-70 parts of silica sol, 10-15 parts of color powder, 10-20 parts of anti-cracked ceramic filler and 1-5 parts of wear-resistant filler.

[0033] In some more preferred implementation cases, in the silica sol color paste: the silica sol is selected from alkaline silica sol and acidic silica sol, and the solid content is 30-35%; the color powder is inorganic color powder such as titanium dioxide, carbon black, and iron oxide; the anti-crushing filler is selected from whisker silicon, whisker aluminum oxide and whisker silicon nitride; the wear-resistant filler is selected from silicon carbide and corundum.

[0034] In some preferred implementation cases, in the primer coating: the siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; the acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; the leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; the non-stick additive is selected from methyl silicone oil, low molecular weight hydroxyl-terminated methyl silicone oil (molecular weight between 300 and 2000); the silane coupling agent is selected from KH-550, KH-560 and KH-570.

[0035] The topcoat coating comprises the following raw materials in parts by weight: 45-70 parts of silica sol, 13-21 parts of siloxane, 1-3 parts of acid catalyst, 1-2 parts of leveling agent and 2-5 parts of non-stick auxiliary agent.

[0036] In some preferred implementation cases, in the topcoat coating: the silica sol is alkaline silica sol; the siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; the acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; the leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; the non-stick additive is selected from methyl silicone oil and low molecular weight hydroxyl-terminated methyl silicone oil (molecular weight between 300 and 2000).

[0037] Secondly, a method for preparing a highly wear-resistant inorganic non-stick coating comprises the following steps: 1) Preparation of primer coating: Mix the silica sol color paste with the acid catalyst, add the leveling agent, silane coupling agent, non-stick additive and siloxane, stir and ripen to obtain the primer coating.

[0038] In some preferred implementation cases, in 1), the preparation method of the silica sol color paste comprises: mixing and ball-milling the silica sol, color powder, anti-crushing filler and wear-resistant filler to obtain the silica sol color paste.

[0039] In some preferred implementation cases, in 1), the stirring and aging rotation speed is 240-260 rpm and the time is 4-6 hours.

[0040] 2) Preparation of topcoat: Mix the silica sol and the acid catalyst, add siloxane, leveling agent, and non-stick additive, stir and mature to obtain the topcoat.

[0041] In some preferred implementation cases, in 2), the stirring and aging rotation speed is 240-260 rpm and the time is 4-6 hours.

[0042] Finally, the application of a layer of highly wear-resistant inorganic non-stick coating in the preparation of a non-stick coating for cookware includes the following steps: sandblasting and cleaning the cookware substrate, preheating, spraying at least 2 layers of primer coating, wet spraying at least 1 layer of topcoat coating, drying, sintering, and obtaining a highly wear-resistant inorganic non-stick coating.

[0043] In some preferred implementation cases, the preheating temperature is 40-60°C.

[0044] In some preferred implementation cases, the primer coating and the topcoat coating are pre-filtered through a 300-500 mesh filter.

[0045] In some preferred implementation cases, the number of spray layers of the primer coating is 2-3 layers, and the number of wet spray layers of the topcoat coating is 1-2 layers.

[0046] In some preferred implementation cases, the drying temperature is 140-160° C. and the drying time is 3-10 min.

[0047] In some preferred implementation cases, the sintering temperature is 240-280° C. and the sintering time is 5-20 min.

[0048] Specific Examples and Comparative Examples Silica sol color paste example: Example 1 65g of alkaline silica sol, 13g of carbon black, 17g of whisker silicon and 5g of silicon carbide were placed in a grinding kettle, and 70g of zirconium beads were added for grinding. The speed was set to 500rpm. After grinding for 4h, the particle size was detected by a fineness meter and was less than 20μm, thereby obtaining a silica sol color paste.

[0049] Comparative Example 1 65g of alkaline silica sol, 16g of carbon black and 19g of whisker silicon were placed in a grinding kettle, and 70g of zirconium beads were added for grinding. The rotation speed was set to 500rpm. After grinding for 4h, the particle size was detected by a fineness meter and was less than 20μm, thereby obtaining a silica sol color paste.

[0050] Comparative Example 2 65g of alkaline silica sol, 13g of carbon black, 12g of whisker silicon and 10g of silicon carbide were placed in a grinding kettle, and 70g of zirconium beads were added for grinding. The speed was set to 500rpm. After grinding for 4h, the particle size was detected by a fineness meter and was less than 20μm, thereby obtaining a silica sol color paste.

[0051] Coating preparation example: Example 2 54.6 g of the silica sol color paste prepared in Example 1 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.62. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared for 4 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, and 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] n CH3, n=40-70, molecular weight 3000-5000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is cured for 4 hours. Then the aluminum plate is sandblasted and cleaned, and then preheated to 50°C. The already cured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate for 3 layers, and then 1 layer of topcoat is wet sprayed, and the surface is dried in a 150°C oven for 5 minutes, and then moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain a highly wear-resistant inorganic non-stick coating with excellent performance.

[0052] Comparative Example 3 The only difference from Example 2 is that when preparing the primer coating, the silica sol color paste of Example 1 is replaced with the same amount of silica sol color paste of Comparative Example 1, and the remaining steps, materials and composition are consistent with those of Example 2, which specifically include: 54.6 g of the silica sol color paste prepared in Example 2 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.64. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared for 4 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, and 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is matured for 4 hours. Then the aluminum plate is sandblasted and cleaned, and preheated to 50°C. The already matured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate for 3 layers, and then 1 layer of topcoat is wet sprayed. The surface is dried in a 150°C oven for 5 minutes, and then moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain an inorganic non-stick coating.

[0053] Comparative Example 4 The only difference from Example 2 is that when preparing the primer coating, the silica sol color paste of Example 1 is replaced with the same amount of silica sol color paste of Comparative Example 2, and the remaining steps, materials and composition are consistent with Example 2, which specifically include: 54.6 g of the silica sol color paste prepared in Example 3 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.6. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared for 4 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, and 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] nCH3, n = 40-70, molecular weight 3000-5000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is matured for 4 hours. Then the aluminum plate is sandblasted and cleaned, and preheated to 50°C. The already matured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate for 3 layers, and then 1 layer of topcoat is wet sprayed. The surface is dried in a 150°C oven for 5 minutes, and then moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain an inorganic non-stick coating.

[0054] Example 3 The only difference from Example 2 is that when preparing the primer coating, 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000) was replaced with 2.8g hydroxy silicone oil (structural formula HO[-Si(CH3)2-O-] n OH, n = 5-30, molecular weight 300-2000), 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000) was replaced with 3.6 g hydroxy silicone oil (structural formula HO[-Si(CH3)2-O-] n OH, n=5-30, molecular weight 300-2000), the remaining steps and materials and composition are consistent with those in Example 2, which specifically include: 54.6 g of the silica sol color paste prepared in Example 1 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.61. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of hydroxy silicone oil (structural formula: HO[-Si(CH3)2-O-] n OH, n = 5-30, molecular weight 300-2000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared for 4 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, 3.6g hydroxy silicone oil (structural formula HO[-Si(CH3)2-O-] nOH, n = 5-30, molecular weight 300-2000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is matured for 4 hours. Then, the aluminum plate is sandblasted and cleaned, and then preheated to 50°C. The already matured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate in 3 layers, and then a layer of topcoat is wet-sprayed, and the surface is dried in a 150°C oven for 5 minutes, and then moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain an inorganic non-stick coating.

[0055] Comparative Example 5 The only difference from Example 2 is that the aging time of the primer coating is increased from 4 hours to 5 hours, and the aging time of the topcoat coating is increased from 4 hours to 5 hours. The remaining steps, materials and compositions are consistent with those of Example 2, which specifically include: 54.6 g of the silica sol color paste prepared in Example 1 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.62. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared for 5 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, and 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] n CH3, n=40-70, molecular weight 3000-5000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is cured for 5 hours. Then the aluminum plate is sandblasted and cleaned, and preheated to 50°C. The cured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate in 3 layers, and then 1 layer of topcoat is wet-sprayed, placed in a 150°C oven for surface drying for 5 minutes, and moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain a highly wear-resistant inorganic non-stick coating with excellent performance.

[0056] Comparative Example 6 The only difference from Example 2 is that the aging time of the primer is reduced from 4 hours to 3 hours, and the aging time of the topcoat is reduced from 4 hours to 3 hours. The remaining steps, materials and compositions are consistent with those of Example 2, which specifically include: 54.6 g of the silica sol color paste prepared in Example 1 and 3 g of 25% formic acid solution were added to the reaction bottle, mixed and stirred, and the pH value was 3.62. Then 1.8 g of polydimethylsiloxane, 4.2 g of KH-560, and 2.8 g of methyl silicone oil (structural formula: CH3[-Si(CH3)2-O-] n CH3, n = 40-70, molecular weight 3000-5000), 20.8g methyltrimethoxysilane was added thereto, the rotation speed was adjusted to 260rpm, and the primer coating was prepared after aging for 3 hours. 48.2g alkaline siloxane silica sol and 2.1g 50% formic acid were added to the reaction bottle, mixed and stirred, and the pH was measured to be 3.6. Then 18.2g methyltrimethoxysilane, 1.4g polydimethylsiloxane, and 3.6g methyl silicone oil (structural formula CH3[-Si(CH3)2-O-] n CH3, n=40-70, molecular weight 3000-5000) is added thereto, the rotation speed is adjusted to 260rpm, and the topcoat is cured for 3 hours. Then the aluminum plate is sandblasted and cleaned, and then preheated to 50°C. The cured primer and topcoat are filtered through a 400-mesh filter and poured into the spray gun bin. First, the primer is evenly sprayed on the substrate for 3 layers, and then 1 layer of topcoat is wet-sprayed. The surface is dried in a 150°C oven for 5 minutes, and then moved to a 260°C oven for high-temperature sintering for 10 minutes to obtain a highly wear-resistant inorganic non-stick coating with excellent performance.

[0057] Performance Testing The high wear-resistant non-stick coating based on silica sol and siloxane prepared in Examples 2-3 and the coating prepared in Comparative Examples 3-6 were tested for hardness, adhesion, wear resistance, non-stick after wear resistance and other properties, wherein the hardness test was carried out in accordance with GB / T 6739, and the results were evaluated as follows: paint film scratches; adhesion test was carried out in accordance with GB / T 9286, with a spacing of 2mm; wear resistance test was carried out in accordance with GB / T1768-2006. The scouring pad was pressed with an abrasion tester for wet abrasion until scratches showing the bottom appeared, and the number of times was recorded. The non-stick after abrasion test was carried out in accordance with GB / T 1768-2006. After each 1000 times of abrasion, the oil-free fried egg test was carried out, and the egg passed if it could be taken out intact, and the number of times was recorded.

[0058] : Table 1: Performance test results of products of Examples 2-3 and Comparative Examples 3-6: Case hardness Adhesion Wear resistance Non-stick after wear resistance Example 2 9H Level 0 120,000 times 2000 times Comparative Example 3 9H Level 0 17000 times 0 times Comparative Example 4 9H Level 1 94000 times 1000 times Example 3 9H Level 0 120,000 times 17000 times Comparative Example 5 8H Level 0 8000 times 0 times Comparative Example 6 7H Level 2 3000 times 0 times From the comparison of the data in the above table, we can see that: Comparative Example 3 uses the silica sol color paste prepared in Comparative Example 1 without wear-resistant filler (silicon carbide). Due to the lack of wear-resistant filler protection in the system, the coating is easily damaged after multiple frictions and leaks out of the substrate, indicating that adding an appropriate amount of wear-resistant filler to the coating can effectively improve the wear resistance of the coating.

[0059] Comparative Example 4 uses the silica sol color paste prepared with the high amount of wear-resistant filler prepared in Comparative Example 2. Due to the increase in wear-resistant filler, the amount of whisker silicon and color powder needs to be reduced accordingly. Too little color powder will result in an inability to effectively cover the substrate and affect the appearance. Therefore, the proportion of whisker silicon is reduced. It can be seen from the test that the coating lacks structures such as whiskers that penetrate the coating, so porcelain collapse will occur when scratched.

[0060] Example 3 uses a small molecular weight hydroxyl-terminated methyl silicone oil to replace the ordinary methyl silicone oil. This will make the silicone oil no longer physically fixed on the coating surface, but condense with the coating network and bond to the coating, thus avoiding being washed away during cleaning, and can effectively improve the long-term non-stick performance of the coating.

[0061] Comparative Example 5 prolongs the aging time of the coating. From the test results, it can be seen that the hardness and wear resistance of the coating are significantly reduced when it is over-aged, and some fine particles will appear on the coating surface. These are all due to the over-aging of the coating, and preliminary agglomeration has occurred in the reaction bottle.

[0062] Comparative Example 6 shortens the aging time of the coating. From the test results, it can be seen that the hardness, adhesion and wear resistance of the coating are significantly reduced due to insufficient aging. This may be due to insufficient hydrolysis of the siloxane in the coating and insufficient condensation between the silanol groups, resulting in a loose network structure formed after film formation.

[0063] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A highly wear-resistant inorganic non-stick coating, characterized in that The invention comprises the following raw materials in parts by weight: Primer coating: 50-75 parts of silica sol color paste, 10-20 parts of siloxane, 1-3 parts of acid catalyst, 3-7 parts of silane coupling agent, 1-2 parts of leveling agent, 2-5 parts of non-stick additive; Topcoat: 45-70 parts of silica sol, 13-21 parts of siloxane, 1-3 parts of acid catalyst, 1-2 parts of leveling agent, 2-5 parts of non-stick additive; In the primer coating: the silica sol color paste comprises the following raw materials in parts by weight: 40-70 parts of silica sol, 10-15 parts of color powder, 10-20 parts of anti-crack filler and 1-5 parts of wear-resistant filler.

2. The highly wear-resistant inorganic non-stick coating according to claim 1, characterized in that: In the silica sol color paste: The silica sol is selected from alkaline silica sol and acidic silica sol, and has a solid content of 30-35wt%; The toner is an inorganic toner; The anti-crack filler is selected from whisker silicon, whisker aluminum oxide and whisker silicon nitride; The wear-resistant filler is selected from silicon carbide and corundum.

3. The highly wear-resistant inorganic non-stick coating according to claim 1, characterized in that: In the primer coating: The siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; The acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; The leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; The non-stick aid is selected from methyl silicone oil and low molecular weight hydroxyl-terminated methyl silicone oil with a molecular weight of 300 to 2000; The silane coupling agent is selected from KH-550, KH-560 and KH-570.

4. The highly wear-resistant inorganic non-stick coating according to claim 1, characterized in that: In the topcoat coating: The silica sol is alkaline silica sol; The siloxane is selected from methyltrimethoxysilane, ethyltrimethoxysilane and phenyltrimethoxysilane; The acid catalyst is selected from formic acid solution, acetic acid solution and hydrochloric acid solution; The leveling agent is selected from polydimethylsiloxane and polymethylphenylsiloxane; The non-stick auxiliary agent is selected from methyl silicone oil and low molecular weight hydroxyl-terminated methyl silicone oil with a molecular weight of 300 to 2000.

5. A method for preparing the highly wear-resistant inorganic non-stick coating according to any one of claims 1 to 4, characterized in that include: 1) Preparation of primer coating: Mix the silica sol color paste with the acid catalyst, add the leveling agent, silane coupling agent, non-stick additive and siloxane, stir and ripen to obtain the primer coating; 2) Preparation of topcoat: Mix the silica sol and the acid catalyst, add siloxane, leveling agent, and non-stick additive, stir and mature to obtain the topcoat.

6. The preparation method according to claim 5, characterized in that: 1), the preparation method of the silica sol color paste comprises: mixing and ball-milling the silica sol, color powder, anti-crushing filler and wear-resistant filler to obtain the silica sol color paste.

7. The preparation method according to claim 5, characterized in that: 1), the stirring and aging speed is 240-260 rpm and the time is 4-6 hours; 2), the stirring and aging process has a rotation speed of 240-260 rpm and a time of 4-6 hours.

8. Use of the highly wear-resistant inorganic non-stick coating according to any one of claims 1 to 4 or the highly wear-resistant inorganic non-stick coating obtained by the preparation method according to any one of claims 5 to 7 in the preparation of non-stick coatings for cookware, characterized in that include: The cookware substrate is sandblasted, cleaned, preheated, sprayed with at least 2 layers of primer coating, and then wet-sprayed with at least 1 layer of topcoat coating, dried, and sintered to obtain a highly wear-resistant inorganic non-stick coating.

9. The use according to claim 8, characterized in that: The number of spray layers of the primer coating is 2-3 layers, and the number of wet spray layers of the topcoat coating is 1-2 layers.

10. The use according to claim 8, characterized in that: The preheating temperature is 40-60°C; The primer and topcoat are filtered through a 300-500 mesh filter in advance; The drying temperature is 140-160°C and the drying time is 3-10 minutes; The sintering temperature is 240-280° C. and the sintering time is 5-20 min.

Citation Information

Patent Citations

  • Water-based inorganic ceramic coating and spraying method thereof

    CN114634759A

  • High-temperature-resistant long-acting non-stick ceramic coating and preparation method thereof

    CN115322598A

  • Long-term high-temperature-resistant non-stick ceramic coating, preparation method and non-stick coating prepared from long-term high-temperature-resistant

    CN117343559A

  • Non-stick ceramic coating and preparation method thereof as well as barbecue tool and preparation method thereof

    CN118638477A